Recherche littéraire/Literary Research Fall 2019 - Maufort, Marc (Recherche littéraire / Literary Research, 2019)
Daniel Acke, Mark Anderson, Eugene L. Arva, Franca Bellarsi, Valérie-Anne Belleflamme, Thomas Buffet, Ipshita Chanda, Mateusz Chmurski, Wiebke Denecke, Christophe Den Tandt, Lieven D'hulst, César Domínguez, Manfred Engel, Dorothy Figueira, John B. Forster, Massimo Fusillo, Gerald Gillespie, Marie Herbillon, S. Satish Kumar, François Lecercle, Ursula Lindqvist, Jocelyn Martin, Jessica Maufort, Marc Maufort, Sam McCracken, Isabelle Meuret, Delphine Munos, Daniel-Henri Pageaux, Danielle Perrot-Corpet, Frank Schulze-Engler, Monica Spiridon, Jüri Talvet, Daria Tunca, Cyril Vettorato, Hein Viljoen, Jenny Webb